GATA4-targeted compounds induce apoptosis and diminish viability of hepatoblastoma cells - Sini M. Kinnunen; Katja Eloranta; Marjut Pihlajoki; Mika J. Välimäki; Saana Pohjavaara; Emilie Indersie; Stefano Cairo; Aarni Kuusinen; Heikki Ruskoaho; Markku Heikinheimo (PLoS ONE, 2026)
Hepatoblastoma is the most common pediatric liver tumor, and it primarily affects young children. Despite improved treatment results due to modern chemotherapy and advanced surgical techniques, there is urgent need to improve the long-term prognosis of hepatoblastoma patients. Elevated expression of transcription factor GATA4 has been associated with pro-tumorigenic functions in hepatoblastoma. Herein, we explored the effects of a novel series of GATA4-targeted compounds (3i-2010–3i-2014) in several hepatoblastoma cell models. To this end, we assessed cell viability (2D and 3D), caspase 3/7 activity, cell cycle process with automated fluorescence microscopy, and RNA and protein expression using quantitative PCR, RNA-sequencing, and western blotting after treating cells with GATA4-targeted compounds. The GATA4-targeted compounds reduced hepatoblastoma cell viability but affected also healthy control cells when high doses were applied. Out of the five compounds used, the 3i-2012 was the most potent. This compound induced G0/G1 phase cell cycle arrest, increased caspase activity, and resulted in changes in transcriptome of hepatoblastoma cells. The differentially expressed genes (DEGs) were associated with cell cycle regulation. Transcription factor target analysis demonstrated that a notable proportion of DEGs were likely regulated by GATA4. In conclusion, 3i-2012 decreases hepatoblastoma cell survival by disturbing cell cycle regulation in the tumor cells.